Kontribusi dan Peran Pengelolaan Keuangan Desa untuk Mewujudkan Anggaran Pendapatan dan Belanja Desa yang Transparan dan Akuntabel (Survey pada Perangkat Desa di Kecamatan Ngaglik, Kabupaten Sleman, Yogyakarta) - Anwar, Misbahul; Jatmiko, Bambang (Akmenika, 2014)
The purpose of the study was to provide training in how to create a web-based budgeting that is effective and efficient, providing information technology related trai-ning for village chief or village secretary (officer appointed) , train chief of village or secretary of the village about a strategy to make the financial report and train make good budgeting, train to make document and orderly administration as giving the number/letter code/code/document archiving, and train the chief of village or secretary of village to empowering potential of their village.